2017
DOI: 10.1016/j.rmcr.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

An undiagnosed pleural effusion with surprising consequences

Abstract: We present the case of a 43-year-old Italian woman with a left undiagnosed pleural effusion, which in subsequent months presented a clinically unexpected evolution with the appearance at first of a right wrist tenosynovitis and subsequently a bilateral lung involvement caused by M. Tuberculosis.With this case report, we would like to underline the importance of making a correct diagnosis of any pleural effusion as soon as possible by at least a thoracocentesis. If untreated, tuberculosis may easily disseminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…The main message of this study is that if thoracoscopy had not been performed, a diagnosis of pleural TB would have been achieved in 15 out of 52 patients (28.8%) and in four of them only with the culture after 30–40 days ( table 3 ). Spontaneous resolution of pleural TB is a well-known phenomenon [ 32 ], but 65% of patients may progress to pulmonary or extrapulmonary TB within 5 years [ 33 , 34 ]. The usefulness of medical thoracoscopy for the diagnosis and treatment of pleural TB has been previously reported [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main message of this study is that if thoracoscopy had not been performed, a diagnosis of pleural TB would have been achieved in 15 out of 52 patients (28.8%) and in four of them only with the culture after 30–40 days ( table 3 ). Spontaneous resolution of pleural TB is a well-known phenomenon [ 32 ], but 65% of patients may progress to pulmonary or extrapulmonary TB within 5 years [ 33 , 34 ]. The usefulness of medical thoracoscopy for the diagnosis and treatment of pleural TB has been previously reported [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The natural history of TB pleural effusion in HIVnegative individuals is a slow resolution without treatment, although, up to 65% will progress to active TB within 5 years [7,8]. However, with HIV-coinfection, progression to active disease is more frequent and occurs faster.…”
Section: Introductionmentioning
confidence: 99%
“…Inappropriate treatment in tuberculous pleural effusion will produce partial healing or development of pulmonary/extra-pulmonary TB within a few years 15 . Casalini et al reported a patient with tuberculous pleural effusion who did not receive ATD and later developed wrist tenosynovitis and pulmonary tuberculosis within the next three months 16 . Loh et al reported 20 tuberculous pleural effusion cases with moderatelarge pleural effusion who received two months of daily isoniazid, rifampicin, pyrazinamide with or without ethambutol or streptomycin followed by four months of a daily or three times a week of isoniazid and rifampicin.…”
Section: Discussionmentioning
confidence: 99%